A development study for liquid- and vapor-fed anode zero-gap bioelectrolysis cells - Nils Rohbohm; Largus T. Angenent (iScience, 2025)
Summary: Improving microbial electrosynthesis could be one solution for transitioning toward sustainable chemical production, offering a pathway to convert CO2 into valuable commodities from renewable energy sources. Therefore, we further developed liquid- and vapor-fed anode zero-gap bioelectrochemical cells for electromethanogenesis, utilizing a membrane electrode assembly to enhance mass and ohmic transport. Focusing on CH4 and H2 production, we tested two ion-exchange membranes with the liquid-fed anode system and selected the best-performing ion-exchange membrane for the vapor-fed anode system. The liquid-fed anode system did not show considerable differences in volumetric CH4 production rates compared to vapor-fed anode systems. However, the latter demonstrated advantages in reducing electrocatalyst degradation and maintaining stable cell voltages, resulting in the highest reported maximum CH4 production efficiency of 48.7 L kWh−1, thus far. The research underscores the need for further optimization to address performance losses and suggests potential for industrial applications of microbial electrosynthesis, highlighting the importance of catalyst protection.